Expression of the curculin gene from different organs of Curculigo latifolia under different culture conditions - Muslihatin, Wirdhatul; Fajar, Nur Syamsiatul; Wibowo, Anjar Tri; Manuhara, Yosephine Sri Wulan (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2025)
Curculigo latifolia is the main source of curculin. Curculin is a special kind of protein that tastes sweet and can change the way food tastes, and is naturally expressed in fruit. This study aims to measure and compare the relative expression of the curculin gene in different organs, i.e., fruit and leaf, under in vitro and in vivo conditions. In this study, mRNA isolation was carried out in tissues derived from fruits and leaves grown in vitro and in vivo (in the soil) of C. latifolia from West Java, Indonesia. Leaves from 20 weeks seedling on polybag, fruit 40 days after anthesis, and leaves from 20 weeks seedling of C. latifolia cultured on MS0 medium that were used in this experiment. The relative expression was measured using qRT-PCR. The results showed that the comparison of curculigo’s parts in the leaves was lower than in the fruit. The lowest expression was obtained in leaves grown under in vitro conditions at 0.001-fold, while leaves grown in the soil at 0.566-fold compared to curculin gene expression in fruit. This study concludes that the expression of the Curculin gene in fruit is different between the fruit and leaves, and the growth conditions have an influence on Curculin gene expression, where Curculin gene expression under in vitro conditions is lower than expression under in vivo conditions. The curculin is not only expressed in the fruit but also the leaves, so it has the potential to be developed.